From Urban Places to Outdoor Spaces: Field-Tested Practices for Engaging BIPOC Youth and Diversifying Outdoor Recreation - Thomas, Mariko O.; Thomas, Charles H. (Frontiers in Communication, 2022)
This collaborative academic-practitioner perspective piece authored by niece and uncle offers praxis-based tools for research and practice about BIPOC-focused outdoor recreation programs. Drawing from applied work in the field and our own familial ties to outdoor nonprofits, we reflect on lessons from work with the Los Angeles-based nonprofit Outward Bound Adventures (OBA) about diversifying outdoor recreation programming. We find there is a lack of research from the communication discipline on racial diversity in outdoor recreation and call for more attention on this important cause. We also suggest five important strategies to working with BIPOC youth in outdoor nonprofits: 1) employ a lens of intersectionality; 2) remind students that “nature” is wherever they are; 3) make change intergenerational; 4) apply “forced” opportunity; and 5) hire leaders reflective of the student population, in hopes of providing potential direction for more research on the subject.